Customized, degradable, functionally graded scaffold for potential treatment of early stage osteonecrosis of the femoral head. Issue 3 (21st August 2017) - Kawai, Toshiyuki; Shanjani, Yaser; Fazeli, Saba; Behn, Anthony W.; Okuzu, Yaichiro; Goodman, Stuart B.; Yang, Yunzhi P.
ABSTRACT: Osteonecrosis of the femoral head (ONFH) is a debilitating disease that results in progressive collapse of the femoral head and subsequent degenerative arthritis. Few treatments provide both sufficient mechanical support and biological cues for regeneration of bone and vascularity when the femoral head is still round and therefore salvageable. We designed and 3D printed a functionally graded scaffold (FGS) made of polycaprolactone (PCL) and β‐tricalcium phosphate (β‐TCP) with spatially controlled porosity, degradation, and mechanical strength properties to reconstruct necrotic bone tissue in the femoral head. The FGS was designed to have low porosity segments (15% in proximal and distal segments) and a high porosity segment (60% in middle segment) according to the desired mechanical and osteoconductive properties at each specific site after implantation into the femoral head. The FGS was inserted into a bone tunnel drilled in rabbit femoral neck and head, and at 8 weeks after implantation, the tissue formation as well as scaffold degradation was analyzed. Micro‐CT analysis demonstrated that the FGS‐filled group had a significantly higher bone ingrowth ratio compared to the empty‐tunnel group, and the difference was higher at the distal low porosity segments. The in vivo degradation rate of the scaffold was higher in the proximal and distal segments than in the middle segment. Histological analysis of both non‐decalcified and calcified samples clearly indicated new bone ingrowth and bone marrow‐containing bone formation across the FGS. A 3D printed PCL‐β‐TCP FGS appears to be a promising customized resorbable load‐bearing implant for treatment of early stage ONFH. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1002–1011, 2018.